Impact of Celebrity Endorsers and Youtube Digital Advertising on Purchase Intention with Brand as A Mediating Variable (A Study on Bella Chocolate) - Wahyudi, Wahyudi; Nurmahdi, Adi (International Journal of Economics (IJEC), 2024)
This research aims to analyse the impact of Endorsers and Digital YouTube advertising on brand awareness and purchase intention, with brand awareness as a mediating variable. The study involved 400 respondents residing in Jabodetabek who had watched Bella Chocolate ads on YouTube but had not yet purchased the product. The methodology used was purposive sampling with analysis utilizing structural equation modelling (SEM) partial least squares (PLS). The findings indicate that Digital YouTube advertising significantly influences brand awareness and purchase intention, whereas Endorsers do not show significant influence on both variables. Furthermore, Brand awareness significantly affects Purchase Intention and acts as a strong mediator between Digital YouTube Advertising and Purchase Intention.